Porous FeP/C composite nanofibers as high-performance anodes for Li-ion/Na-ion batteries. (June 2020) - Yang, Y.; Fu, W.; Lee, D.C.; Bell, C.; Drexler, M.; Ma, Z.F.; Magasinski, A.; Yushin, G.; Alamgir, F.M.
Abstract: Iron phosphide (FeP) is regarded as a potential anode for Li/Na-ion batteries due to its high specific capacity. However, the poor electrical conductivity along with a rapid capacity degradation is a barrier for its grid applications. Here, we show that a porous composite nanofiber (NF) with FeP nanoparticles embedded in a conductive carbon matrix can be used as high-performance anodes for Li-ion and Na-ion batteries. The FeP/C composite NFs can be produced by a combination of electrospinning, carbonization, oxidation and phosphidation. As an anode for Li-ion batteries, the composite can exhibit a specific capacity over 1100 mAh g −1, which is 3 times higher than that of commercial graphite anode. Even at a fast charge/discharge rate, it shows stable performance for 1, 000 cycles. It is equally important that the FeP/C composite can be used for Na storage with a specific capacity of up to 760 mAh g −1 along with excellent cycle stability, much better than the FeP particles without carbon matrix. These results emphasize the importance of the rational design of FeP/C composites, in which the carbon matrix can not only enhance charge and ion transport but also minimize the structural changes upon cycling. Graphical abstract: Image 1 Highlights: FeP/C nanofibers were successfully synthesized as anode material. Porous FeP/C composite nanofibers exhibit highly improved lithium and sodium storage performance. Porous C matrix can alleviate the giant volume changes and facilitate fast charge transfer.